Effects of the Combined Use of Styrene-Butadiene-Styrene and Gilsonite in Bitumen Modification on the Stiffness and Thermal Sensitivity of Bitumens - Yamaç, Özge Erdoğan; Yılmaz, Mehmet; Kök, Baha Vural (Fırat University, 2018)
In the present study, the effects of styrene-butadiene-styrene (SBS) and American gilsonite (AG) on the stiffness and thermal sensitivity of bituminous binders were investigated in bitumen modification. Şanlıurfa province was chosen as the application field. It was determined that 18% AG and 5% SBS additives should be used separately to obtain the adequate binder for Şanlıurfa province. It was also determined that 13% AG with 2% SBS, 10% AG with 3% SBS and 6% AG with 4% SBS were required to obtain binders with the same performance level. Penetration, softening point and rotational viscometer tests were conducted on neat and modified bitumen to determine the consistency of binders. Furthermore, thermal sensitivities of binders were determined from penetration index and penetration viscosity number values. It was determined that all additives increased the consistency of the binders, the most effective additive type and ratio was 18% AG on penetration values, and all additives had similar effects on the softening point and viscosity values. In addition, it was determined that the temperature susceptibility was reduced with additive use and the most effective contribution came from 5% SBS.
Keywords: Engineering; Mühendislik